1996
DOI: 10.1192/s0007125000298577
|View full text |Cite
|
Sign up to set email alerts
|

Management of Treatment Refractory Schizophrenia

Abstract: There is a general consensus that 5–25% of schizophrenic patients are partially or totally unresponsive to antipsychotic drug therapy (Brenner et al, 1990). Agreement is needed on how to define the varying degrees of response and resistance in individual patients on conventional antipsychotic medication. Apparent “treatment resistance” may be due to noncompliance; excessive protein binding with inadequate bio-availability of the neuroleptic; an inadequate or excessive dose resulting in poor efficacy or side-ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In such cases, the risk of non-compliance during oral medication is increased and regular appointments in outpatient treatment are more likely to be missed after discharge from hospital. Home-based outpatient treatment has been shown both to increase compliance and reduce the number of relapses compared with conventional individual outpatient treatment [10,18,21,23]. On the other hand, despite efforts to maintain continuity in treatment, schizophrenia is often associated with an increased risk of premature death [3].…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, the risk of non-compliance during oral medication is increased and regular appointments in outpatient treatment are more likely to be missed after discharge from hospital. Home-based outpatient treatment has been shown both to increase compliance and reduce the number of relapses compared with conventional individual outpatient treatment [10,18,21,23]. On the other hand, despite efforts to maintain continuity in treatment, schizophrenia is often associated with an increased risk of premature death [3].…”
Section: Introductionmentioning
confidence: 99%
“…For patients diagnosed with schizophrenia, compliance with medication becomes central to achieve predicted length of stay outcomes on the care pathway. Non-compliance is high within this group of patients with the presence of unpleasant side-effects given as the main reason (Morrison 1996). Kemp et al (1996) found that in-patient compliance and attitudes to medication improved with 4-6 contact sessions compared to a control group and this effect lasted for 6 months post treatment.…”
Section: Nature and Disease Progression Of Schizophreniamentioning
confidence: 80%
“…Currently, mental illness is often managed primarily through medications, but many patients in psychiatric hospitals often prove treatment-resistant to pharmaceutical intervention [5]. However, individualized care in psychiatry is able to significantly improve outcomes in patients [6-7]. What must be further studied and remedied are the institutional and economic problems that in actual practice tend to prevent patients from receiving individualized care.…”
Section: Discussionmentioning
confidence: 99%